The use of student-teachers’ reflections in the improvement of a teaching practice programme at the University of Limpopo - Singh, Suresh Kamar; Mabasa, Layane Thomas (South African Journal of Higher Education, 2016)
Reflections in teacher education and teaching practice in particular are considered to be a crucial aspect to the development of teachers and student teachers. As a result, many teacher training programmes require student teachers to undertake self-reflections. However, there is a complaint that teacher training programmes do not use reflections as they are supposed to be used. It is within this context that the study on which this article is reporting was undertaken looking at the manner in which University of Limpopo’s School of Education uses reflections to improve its teaching practice programme. Data was generated from a questionnaire, focus group interview and documents. The study found that the student-teachers do reflect on their teaching practice even though their reflections were not always incorporated in improving the programme. We argue that reflection should be considered as an enabling condition to improve teaching practice along the lines of engaged, democratic action.